SCREENING FOR ANTIFEEDANT ACTIVITY OF GYMNEMA SYLVESTRE LEAF EXTRACTS AGAINST SPODOPTERA LITURA F. (LEPIDOPTERA: NOCTUIDAE) - CHOUDHARY, JAIPAL SINGH; SRIVASTAVA, CHITRA; WALIA, SURESH (The Bioscan, 2014)
Antifeedant activity of Gymnema sylvestre leaf extracts with different solvents viz., hexane, methanol, chloroform, ethyl acetate, butanol and acetone precipitated were evaluated against third instar larvae of Spodoptera litura through choice as well as no choice methods. Antifeedant activity of various extracts was compared based on their AI50 values. It was observed that saponins mixtures showed lowest AI50 value (0.047%) followed by azadirachtin (0.086%) through no-choice test method observed after 24 hours. When it was tested with choice method, saponins mixture also showed lowest AI50 as 0.036% after 24 hours of treatment. After 48 hours of observation through no-choice and choice method precipitated saponin mixtures of G. sylvestre showed antifeedancy within the fiducial limit of azadirachtin. In the present study precipitated mixture of saponins extracted from G. sylvestre showed very good antifeedant activity, which could be used for the ecofriendly management of lepidopteran insect pests.